Implementasi Metode Quality Function Deployment (QFD) Untuk Merancang Peningkatan Kualitas Pelayanan Pendidikan di Politeknik ‘Aisyiyah Pontianak - Asih, Zwesty Kendah; Akbar, Ahmad; Wahab, Wahab (Jurnal Ilmiah Global Education, 2024)
In order to improve the quality of higher education services at Politeknik 'Aisyiyah Pontianak, an action plan was developed to close the quality gap between perceived expectations and expectations expected by students, as well as the characteristics of higher education service quality desired by students as service users. The Quality Function Deployment (QFD) model is the method used in this study to determine service attributes using the Servqual model. Three general information regarding students' desires, satisfaction, and expectations of service attributes were included in the distributed questionnaires.  In conclusion, from the data processing of twenty educational service quality attributes, there are six attributes that have gaps in educational service quality. These gaps are fast online and offline academic services, easy access to information related to academics, fast and accurate acquisition of academic information, adequate library facilities (the number of collections in the library), adequate Internet facilities (ease of access, browsing speed), complete and adequate laboratory facilities. The action plan for quality improvement is (1) Improving the Academic Service System, (2) Providing a special portal for access to academic information, (3) Improving Academic Information System Services, (4) Improving Library Facilities by adding amount book collections, e-books, e-journals etc., (5) Improving Internet Facilities by adding Bandwitch, (6) Improving Laboratory Facilities.